THBS1 as a candidate biomarker and fibrotic mediator in radiation-induced liver injury: insights from TMT-labeled quantitative proteomics - Wang, Zixi; Wu, Tong; Wang, Haixu; Deng, Yawen; Liu, Jing; Wang, Tingting; Ren, Xue; Sun, Ying; Zhang, Haibo; Yang, Defu; Shang, Feng; Xu, Ying; et al. (Frontiers in Pharmacology, 2025)
ObjectiveRadiation-induced liver injury (RILI) is one of the most dreaded complications in radiotherapy for hepatocellular carcinoma (HCC), causing serious impact on the course of treatment and the survival quality of patients. This study was conducted to screen effective biomarkers for the diagnosis and disease course monitoring of RILI.MethodsThis study established a rat model of RILI, with the assessment of liver injury by hematoxylin-eosin (HE) staining. High-throughput screening of RILI and normal liver tissue samples was performed using TMT quantitative proteomics technology, followed by the analysis of differentially expressed proteins (DEPs) using GO and KEGG. Weighted gene co-expression network analysis (WGCNA) and protein-protein interaction (PPI) network analysis were further employed to identify THBS1 as a key protein of RILI. We knocked down THBS1 in rat (BRL, BRL-3A) and human (THLE-2) hepatocytes using siRNA and applied Ruxolitinib to inhibit the JAK2/STAT3 pathway, further clarifying the role of THBS1 in this signaling process. Validation was performed by protein-protein docking and Western blot. The concentration of THBS1 in plasma was determined using enzyme linked immunosorbent assay (ELISA), while the consistency of plasma and tissue expression was analyzed by Pearson’s correlation analysis.ResultsProteomic analysis identified 176 DEPs, of which 106 were upregulated, with THBS1 identified as a key protein highly expressed in RILI. THBS1 could activate the PDGFA/PDGFR signaling pathway, which in turn leads to the activation of the JAK2/STAT3 pathway, resulting in the deposition of COL5A and COL6A. Silencing THBS1 with siRNA in BRL, BRL-3A, and THLE-2 cells significantly reversed the activation of the JAK2/STAT3 signaling pathway and the overexpression of collagens in the cellular models. In addition, plasma ELISA revealed that the concentration of THBS1 in plasma increased with increasing radiation dose and degree of RILI, which was consistent with the expression level in the liver tissue.ConclusionThis study provides new insights into the pathogenesis of RILI, and identifies THBS1 as a potential biomarker for RILI diagnosis and monitoring.